Changes in land use in Jewish and Arab municipalities, 2003-13. Issue 5 (2nd September 2020) - Shahor, Tal; Simonovich, Javier; Sharabi, Moshe
ABSTRACT: This article compares the amount of land designated for various uses in the Jewish and Arab municipalities in Israel between the years 2003–13. It is generally accepted that the Arab-Jewish conflict in Israel is heavily based on land ownership. This conflict still has implications for the policies and actions of the State of Israel on the one hand, and the attitudes and behaviours of the Arab population on the other. Two main conclusions emerge from this article. The first is that in 2013, the area per capita used for residential living in Arab localities was larger, presumably because of the lack of high-rise buildings. The second conclusion is that the areas designated for economic and public purposes in the Arab sector are much smaller. The Israeli government should therefore allocate additional government land to the Arab local authorities.